Utilización de diferentes niveles de inclusión de harina de alfalfa en raciones suplementarias para vacas en producción en la quinta experimental Punzara de la Universidad Nacional de Loja. - Angamarca Patiño, Jiphson Oswaldo (2018)
This research work was carried out in the Fifth Experimental "Punzara" of the National University of Loja, with the purpose of evaluating rations with different levels of inclusion of alfalfa meal in Holstein mestizo cows kept in pasture. Four rations with different levels of alfalfa meal were evaluated: T1: without alfalfa meal, (control); T2: with 10% alfalfa meal; T3: with 20% of alfalfa flour and T4: with 30% of alfalfa flour. Four mestizo cows of different ages were used, with an average weight of 542.2 kg and an average daily production of 7 liters, with four treatments and four periods. The variables studied were: bromatological composition of the experimental rations; food consumption, milk production, milk quality, weight change and profitability. The results show an appreciable nutritional value of the rations prepared with different inclusion levels of alfalfa meal, with average values ​​of 60.49 for dry matter; 21.91 and 15.63 for protein and crude fiber respectively; likewise, greater consumption of food was evident in treatment three and four (20 and 30% of alfalfa meal), which generated an increase in milk production of 1 l / cow / day in treatment three. With regard to the organoleptic characteristics and the quantification of fat in milk, they were not compromised; however, the protein content evidenced a progressive decrease, being lower in the treatment two (10% HA). Finally, profitability was acceptable for all treatments; so it is concluded that the use of supplementary rations based on alfalfa flour, is a technically and economically viable alternative to improve milk production. Key words: Alfalfa flour, rations, bromatological composition, organoleptic characteristic